2022
DOI: 10.1051/mfreview/2022010
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria decision making in electrical discharge machining with nickel coated aluminium electrode for titanium alloy using preferential selection index

Abstract: In the present scenario, great effort is expended to improve the machining process by adopting multi-criteria decision making in electrical discharge machining (EDM). In this research article, an attempt was made to optimize the process parameters of EDM with Nickel Coated Aluminium Electrode for machining Titanium Alloy using Preference Selection Index (PSI). The experimental work were performed using Taguchi based L16 orthogonal to solve multi-objective optimization problem. The current (I), voltage (U) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Preference Selection Index can be used in determining the relative relationship between attributes if there is a conflict of interest between all attributes [18,19]. The stages of solving multi-criteria decision support problems using the Preference Selection Index, namely [8,9,11]: 1. Determination of the Decision Matrix…”
Section: Preference Selection Index Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preference Selection Index can be used in determining the relative relationship between attributes if there is a conflict of interest between all attributes [18,19]. The stages of solving multi-criteria decision support problems using the Preference Selection Index, namely [8,9,11]: 1. Determination of the Decision Matrix…”
Section: Preference Selection Index Methodsmentioning
confidence: 99%
“…Preference Selection Index is a method that can be used to solve multi-criteria decision-making problems [7][8][9]. Previous research by Depa Supitri, et al [10], Nguyen Huu Phan, et al [11], Aditya Alfiansyah Saragih, et al [12], Usanto S [13], and Agung Sutrisno & Vikas Kumar [14], concluded that the Preference Selection Index method can provide solutions as support in solving multi-criteria decision-making problems objectively through alternative ranking results.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, a number of research studies investigated the PSI method in many MCDM problems It has been used to assess machine performance (Bilgin Sarı, 2019), propose a waste recovery method for electrical/electronic products (Sari, 2020), select an automated system development method for scholarship recipients (Arifin and Saputro, 2022), make decisions regarding tooth restoration/beautification materials (Yadav, 2022), determine life cycle design solutions for product systems (Attri and Grover, 2015), choose technological parameters for turning (Vara Prasad et al, 2018), select parameters for electrical discharge machining (Phan et al, 2022), determine technological parameters for the grinding process (Hoang Tien et al, 2021) and rank types of materials for engineering (Maniya and Bhatt, 2010). Thus, The PSI method has been used well for making complex choices in a lot of different areas.…”
Section: Preference Selection Indexmentioning
confidence: 99%
“…MCDM is a systematic approach used to handle complex decision-making processes by considering several criteria or factors simultaneously. The main purpose of MCDM is to assist decision makers in evaluating decision alternatives and selecting optimal solutions based on predefined criteria [8]. The MCDM method involves mathematical and statistical analysis to measure the relative value of each alternative, which is then used to rank or select the best solution.…”
Section: Introductionmentioning
confidence: 99%